2010
DOI: 10.1002/jmor.10825
|View full text |Cite
|
Sign up to set email alerts
|

Is the large size of the pinna of the ear of the European hare (Lepus europaeus) due to its role in thermoregulation or in anterior capital shock absorption?

Abstract: Large pinnae are characteristic of the Leporids, and the pinna is known to have a thermoregulatory role. Another role has been hypothesized for the pinna of Lepus spp., as a part of a suspensory system for the greater portion of the head, absorbing shock that might otherwise interfere with vision during high-speed locomotion. We compared the lengths of the pinnae of adult European hares Lepus europaeus from the source population in the cooler climate of England with those of the introduced population in the wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Lindstedt & Boyce, 1985) including other lagomorphs (e.g. genus Lepus, Stott, Jennings & Harris, 2010). Moreover, studies from Australia have shown that European rabbits introduced in a warmer environment responded by increasing the mean length of their ears (Parer & Libke, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Lindstedt & Boyce, 1985) including other lagomorphs (e.g. genus Lepus, Stott, Jennings & Harris, 2010). Moreover, studies from Australia have shown that European rabbits introduced in a warmer environment responded by increasing the mean length of their ears (Parer & Libke, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…At rest, the pinna of leporids is a thermoregulatory organ. 74 This is certainly the case with European hares. 69 The Australian population of the European rabbit has responded to its warmer environment by increasing the mean length of its pinna from 71 mm in England and France to 79 mm in Australia.…”
Section: Earmentioning
confidence: 96%
“…Thus, the piriform fenestra and basisphenoid/basioccipital fissure serve as an intracranial joint, which Bramble (1989) suggests helps to dampen forces that occur during the locomotor cycle of lagomorphs, especially in highspeed hares. Due to soft tissue attachments across the intracranial joint, the large ears of hares may also act to support and reset the anterior (ethmoid-orbital) part of the cranium (Stott et al, 2010). Bramble (1989) assumed that in steady quadrupedal running the forelimbs produce a significant braking effect, while the hindlimbs primarily accelerate the body.…”
Section: Cranial Kinesis and Locomotionmentioning
confidence: 99%
“…Beyond those detailed by Bramble (1989), other morphological features of the cranium have been associated with locomotion including a pronounced ventral flexion of the facial region and unique fenestrations in the posterior cranial bones and lateral portion of the maxilla (DuBrul, 1950;Moss and Feliciano, 1977;Stott et al, 2010;Kraatz et al, 2015;Kraatz and Sherratt, 2016). The unique rostral vacuity (Ochotonidae) and fenestration (Leporidae) in lagomorphs were noted by Gray (1867), andDuBrul (1950) suggested that the latticing of the maxilla in Leporidae could increase the efficiency of speedy locomotion by reducing weight of the rostrum, and potentially contributing to Bramble's (1989) anterior capital suspensory system hypothesis.…”
Section: Cranial Biomechanicsmentioning
confidence: 99%